Infectious complications of surgical treatment in long bone methaepiphyseal fractures - Bets, Iryna; Logvin, Andrii; Maliasov, Oleg (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2017)
In recent decades, metalosteosynthesis has been used to treat fractures of bones, the indications to which are rapidly expanding, which is promoted by the spread of AO’s development. Along with this, there is a significant number of complications of metalosteosynthesis, first of all, infection. It is generally believed that complications in the use of internationally recognized AO technologies are associated only with the low professional training of surgeons, which is difficult to accept completely. Objective: to conduct a retrospective analysis of the causes of infectious complications after metalosteosynthesis fractures of distal metaepiphises of long bones and on its basis to determine tactical and technological measures to reduce their number. Methods: the clinical material of the department of bone infection «Kharkiv City Multiprofile Hospital № 18» was used. The study group included 78 patients with infectious complications after osteosynthesis of fractures of distal metaepiphises of long bones. Results: the interaction between infection complications and the chosen tactics of surgical treatment was traced. Among the most likely causes of infectious complications after metalosteosynthesis fractures of the pilon type are either tactical or preoperative planning errors. In the case of open and high-energy injury, distal metaepiphises of long bones is recommended to give preference to extra-osseous methods of osteosynthesis. Conclusions: for the prevention of i infectious complications, advanced understanding of AO technologies in the light of the biological principles of osteosynthesis, careful preoperative planning, technological support of operations, training of surgeons, expanded use of methods of extra-focal fixation with open and high-energy injury is necessary.